SIMULATE THE FLOW IN MONOLITH REACTORS USING CFD - Sharif, Samrana; Al-Dahhan, M. H.; K. Wardag, A. N.; Chughtai, I. R.; Arif, M. (The Nucleus, 2020)
The objective of this research work is to simulate the flow in monolith reactors using computational fluid dynamics for both single channel and monolith bed. It proposes a co-current down flow monolith reactor system to investigate the flow distribution characteristics in a 2 inch monolith reactor equipped with selected types of distributors and operated in the Taylor flow regime. The effects of liquid distributor type and the liquid and gas velocities within the desired flow regime of Taylor flow on the flow distribution have also been investigated and provided. The existing single tube model for the Taylor flow regime has modified by integrating the hydrodynamics and kinetics to predict the performance of monolith reactor. The analysis on both single channel and monolith bed has been done and compared with the experimental data provided.